Factors for Identifying Non-Anthropic Conscious Systems - Castle, Ryan (Cosmos and History: The Journal of Natural and Social Philosophy, 2016)
<!–[if gte mso 9]> <![endif]–> One of the problems of identifying consciousness is defining it in ways that allow for universal application and exploration. Popular and anthropocentric definitions are problematic due to their inherent bias toward exclusively biological events in a field of study that does not require and is even hindered by this limitation. A preliminary definition is needed that would encompass known biological consciousness as well as theoretical macro, micro, and intrinsic levels of consciousness. This paper proposes that the following are a preliminary set of factors for openly exploring what can be considered conscious with no biological or cultural biases. 1. Communication: Consciousness requires discrete parts of the system to be able to influence one another in a holistic manner. Whether this is by synaptic firing or gravitic relationships is irrelevant. 2. Adaptation: Consciousness requires adaptation to its environment. Note the avoidance of the popular term "awareness," which is an untestable factor on many levels. Static systems cannot be conscious. Dynamic systems can be, but are not necessarily conscious. 3. Complexity: In order to be differentiated from purely physical or chemical dynamic systems, conscious systems must display a sufficient complexity in energy rate density. This paper proposes a É¸m (erg/second/gram) of a minimum of 103 for any given system to be considered complex enough to display consciousness. This is equivalent to the simplest lifeforms considered conscious. The first two requirements are easily understood. The requirement of complexity is the least conventional and requires explication. Physical complexity is often used as a basic threshold for organization, but this seems to be due to convenience more than logical applicability, especially when informational systems are weighed on their quantitative value. It does not follow that a greater number of components translates to a higher threshold of complexity, any more than saying a bucket of sand is more physically complex than an iPad because it has more particulates. As Eric Chaisson posits, energy rate density is a more universal and reliable means of organizing complexity. Energy rate density (ERD) measures the energy flow in ergs per gram per second within a given system. This qualitative assessment of energy efficiency is more insightful than listing non-adaptive arrangements such as physical interactions or even systems theory. The dramatic spike in ERD for all known conscious systems makes this an ideal metric for exploring radically different systems about which little else is known. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>